The validity of the Push Band 2.0 during vertical jump performance - Lake, J. P.; Augustus, S.; Austin, K.; Mundy, P.; McMahon, J. J.; Comfort, P.; Haff, G. G. (Sports, 2018)
The Push Band has the potential to provide a cheap and practical method of measuring velocity and power during countermovement vertical jumping (CMJ). However, very little is known about whether it conforms to laboratory-based gold standards. The aim of this study was to assess the agreement between peak and mean velocity and power obtained from the belt-worn Push Band, and derived from three-dimensional motion capture, and vertical force from an in-ground force platform. Twenty-two volunteers performed 3 CMJ on a force platform, while a belt-worn Push Band and a motion capture system (a marker affixed to the Push Band) simultaneously recorded data that enabled peak and mean velocity and power to be calculated and then compared using ordinary least products regression. While the Push Band is reliable, it tends to overestimate peak (9-17%) and mean (24-27%) velocity, and when compared to force plate-derived peak and mean power, it tends to underestimate (40-45%) and demonstrates fixed and proportional bias. This suggests that while the Push Band may provide a useful method for measuring peak and mean velocity during the CMJ, researchers and practitioners should be mindful of its tendency to systematically overestimate and that its measures of peak and mean power should not be used.